Peningkatan Kemampuan Digital Storynomics Tourism Dalam Implementasi Wisata Edukasi Berkelanjutan Di Desa Sirnajaya Kecamatan Sukamakmur Kabupaten Bogor - Wibowo, Setiawan; Yatimah, Durotul; Sasmita, Karta; Darmawan, Daddy; Tijari, Ahmad (Jurnal Pemberdayaan Pariwisata; Vol 6 No 2 (2024): Jurnal Pemberdayaan PariwisataDO - 10.30647/jpp.v6i2.1851, 2024)
Community-based tourism is an approach in tourism development that actively involves and empowers local communities throughout the entire tourism process, from planning to managing tourism destinations. This approach aims to enhance the tourism awareness capacity of the community through the implementation of Digital Storynomics Tourism in Sirnajaya Village, Sukamakmur District, Bogor Regency. Digital Storynomics Tourism is an innovative approach that combines digital technology and local stories to increase community awareness and participation in the tourism sector. This training uses participatory methods, involving local communities in developing digital content that promotes the uniqueness and tourism potential of Sirnajaya Village by utilizing social media platforms and digital technology. The training results show a significant increase in the community's tourism awareness capacity, as well as an increase in tourism activities and community participation in promoting local destinations. The implementation of Digital Storynomics Tourism in Sirnajaya Village serves as a model that can be applied in other areas to strengthen community involvement in sustainable tourism development. Keywords: educational tourism, storynomics tourism, local potential